Studi Pemberian Bokashi Jerami Padi terhadap Gejala Penyakit Tanaman Kacang Edamame (Glycine max (L.) Merill) - Wati, Sylvianoor Milla; Heiriyani, Tuti; Aziza, Noor Laili (Universitas Lambung Mangkurat, 2023)
Edamame beans (Glycine max (L.) Merill) are a food crop commodity that is very popular with Indonesians as a source of vegetable protein. One of the causes of low soybean yields in Indonesia is due to plant diseases. In cultivation activities, fertilization has an important role to fulfill plant nutrient needs. In this study, the fertilizer used was rice straw bokashi. This study aims to determine the effect of giving rice straw bokashi on disease symptoms of edamame bean plant (Glycine max (L.) Merill), knowing what percentage of edamame bean plant (Glycine max (L.) Merill) is symptomatic by giving rice straw bokashi and for identify the type of disease based on the symptoms found in edamame bean (Glycine max (L.) Merill) by giving rice straw bokashi. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, carried out from July 2020 to October 2020. This research method used a randomized block design (RAK) 1 factor, namely the dose of rice straw bokashi. The treatment doses used were K0: 0 t ha-1 (control), K1: 5 t ha-1 equivalent to 2 kg / plot, K2: 10 t ha-1 equivalent to 4 kg / plot, and K3: 15 t ha.-1 is equivalent to 6 kg / plot. The treatment was repeated five times, in order to obtain 20 experimental units. The results showed that the use of rice straw bokashi fertilizer had no significant effect on disease attack on edamame beans (Glycine max (L.) Merill). The highest percentage of disease attack was found in the fourth week ofall treatments with 99 to 100% disease attack. In the number of types of diseases, it is known that in the first week there is no disease that attacks the edamame bean (Glycine max (L.) Merill). In the second week to the fourth week of the K0 treatment (rice straw bokashi 0 t ha-1 (control)), there were types of false dew, powdery mildew, stunted disease, and cowpea faint patches (CMMV). Treatment K1 (rice straw bokashi 5 t ha-1 equivalent to 2 kg / plot) contained false dew, bacterial wilt, leaf blight, leaf rust, dwarfism, and cowpea faint patches (CMMV). K2 treatment (rice straw bokashi 10 t ha-1 equivalent to 4 kg / plot) there are types of false dew, powdery mildew, leaf rust, stunts and cowpea faint patches (CMMV). Treatment of K3 (rice straw bokashi 15 t ha-1 equivalent to 6 kg / plot) contained false dew, powdery mildew, dwarfism, leaf blight, leaf rust, and cowpea faint patches (CMMV).